Disaggregation of Ploidy, Gender, and Genotype Effects on Wood and Fiber Traits in a Diploid and Triploid Hybrid Poplar Family - Huang, Xu-Yan; Shang, Jing; Zhong, Yu-Hang; Li, Dai-Li; Song, Lian-Jun; Wang, Jun (Frontiers in Plant Science, 2022)
Triploid breeding based on unilateral sexual polyploidization is an effective approach for genetic improvement of Populus, which can integrate heterosis and ploidy vigor in an elite variety. However, phenotypic divergence of unselected allotriploids with the same cross combination remains poorly understood, and contributions of ploidy, gender, and genotype effects on phenotypic variation are still unclear. In the present study, wood and fiber traits, including basic density (BD), lignin content (LC), fiber length (FL), fiber width (FW) and fiber length/width (FL/W), were measured based on a 10-year-old clonal trial including full-sib diploid and triploid hybrids of (Populus pseudo-simonii × P. nigra ‘Zheyin3#’) × P. × beijingensis, and contributions of ploidy, gender, and genotype effects on variation of these traits were disaggregated to enhance our understanding of triploid breeding. We found significant phenotypic variation for all measured traits among genotypes. All the wood and fiber traits studied here underwent strong clonal responses, with high repeatabilities (0.55–0.76). Pearson’s correlation analyses based on best linear unbiased predictors (BLUPs) revealed that BD was significantly positively correlated with FL (r = 0.65, p = 0.030), suggesting that BD could be improved together with FL during triploid breeding. The FL of triploids was significantly larger than that of diploids (p < 0.001), suggesting that ploidy strongly affected the variation of FL traits. Difference between females and males was not significant for any measured trait, implying that gender might not be a major factor for variation in these traits. Further analyses of variance components showed that genotype dominantly contributed to the variation of BD, LC and FW traits (with 54%, 62% and 53% contributions, respectively) and ploidy contributed strongly to variation in FL and FL/W (77% and 50%, respectively). The genetic coefficient of variation (CVG) of triploids for each trait was low, suggesting that it is necessary to produce a large number of triploids for selection or to use different Populus species as parents. Our findings provide new insights into the genetic effects of ploidy, gender and genotype on wood and fiber traits within a full-sib poplar family, enhancing the understanding on the triploid breeding program of Populus.